Accelerated Corneal Cross-Linking With a Hypoosmolar Riboflavin Solution in Keratoconic Thin Corneas: Short-Term Results. Issue 3 (March 2016) - Koç, Mustafa; Uzel, Mehmet Murat; Koban, Yaran; Tekin, Kemal; Taşlıpınar, Ayşe Güzin; Yılmazbaş, Pelin
Abstract : Purpose: The aim of this study was to evaluate the early term topographic and aberration results of accelerated (9 mW/cm 2 ) corneal cross-linking (CXL) treatment in keratoconic thin corneas. Methods: Forty-nine eyes from 43 patients (mean age of 21.2 ± 7.1) with progressive keratoconic thin corneas (<400 μm without epithelium) who had accelerated corneal CXL with hypoosmolar riboflavin solution throughout the procedure were enrolled. We measured the uncorrected and corrected distance visual acuity, refraction, slit-lamp examination, topographic values, and corneal higher-order aberrations (Pentacam HR, Oculus Optikgeräte GmbH) preoperatively and 1, 3, and 6 months after surgery. Results: Before surgery, the corneal thickness was 404 ± 18 μm, and the thickness was reduced to 360 ± 24 μm after removing the epithelium. After the application of hypoosmolar riboflavin solution, the thickness increased to 432 ± 44 μm. At month 6, there was a significant increase in uncorrected distance visual acuity ( P = 0.043) and corrected distance visual acuity ( P = 0.024), a decrease in spherical refraction ( P = 0.041), maximum keratometry (Kmax, P = 0.003), anterior elevation values ( P = 0.008), corneal thickness ( P < 0.001), coma ( P = 0.022), spherical aberration ( P = 0.001), higher-order root mean square ( P = 0.004), and total root mean square ( P < 0.001), whereas the cylindrical refraction ( P = 0.627), anterior ( P = 0.665) and posterior astigmatism ( P = 0.165) of the cornea, posterior elevation ( P = 0.198), and trefoil ( P = 0.141) remained unchanged. No patients showed any complications or scar formation during follow-up. Conclusions: Accelerated corneal CXL with hypoosmolar riboflavin solution throughout the procedure is effective in thin corneas.